La lúdica como estrategia didáctica para el fortalecimiento de la prevención en la salud oral de menores en etapa escolar - Paredes Posada, Estefania; Lozano Tabares, Angie Lorena; Ana Lucía, Ramírez Bohórquez; José Yesid, Ramírez Bohórquez (Universidad Antonio Nariño, 2024)
Objective: to determine the modification of a specific playful educational strategy "Smiling Chameleon Take Care of Your Teeth" to strengthen the promotion of oral health.